PHOTO-ASSISTED DEGRADATION OF 3-MERCAPTOPROPIONIC ACID BY FENTON REAGENT - Kumar, Dharmendra (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Objectives: The main objective of the research were to develop an energy saver, cheaper eco-friendly method for removal of pollutants, because another process needing a large consumption of energy, time and produce harmful byproducts. This process may used to eliminate toxic and bioresistant organic and inorganic pollutants through their transformation into harmless species. Thiol compounds are widely used in pharmaceuticals and agrochemicals. These chemicals has high risk bracket for human health diseases like, corrosive to skin, eyes, respiratory system, chemical burns, irritation, ulcers etc. Methods: The Photo-assisted degradation of 3-Mercaptopropionic acid by Fenton reagent has been investigated. The effect of various reaction parameters such as conc. of substrate, conc. of H2O2, conc. of FeSO4, pH, polarity of solvent and catalyst variation on the rate of photocatalytic process has been studied. Results: The control experiments were performed. The reaction was carried out in the presence of Fenton reagent, oxygen and light. Advanced oxidation processes (AOPs) have proved superiority over the conventional techniques like precipitation, flocculation, filtration, incineration or the biological pathways. These methods are based on the principle of generation of highly reactive hydroxyl radical, which is capable for destruction of pollutants. The Photoproduct 3,3'-dithiodipropionic acid was characterized by physical, chemical and spectral methods. A tentative mechanism has been proposed with overall reaction. Conclusion: This research method is promising and eco-friendly for removal of pollutants from wastewater. The treated water may be used for daily purpose like irrigation and cleaning etc. Keywords: Photosensitized oxidation, 3-Mercaptopropionic acid, Fenton and photo-Fenton reagent.